Occurrence of Noctiluca scintillans bloom off Mangalore in the Arabian Sea - Sulochanan, Bindu; Dineshbabu, A. P.; Saravanan, Raju; Subramanya Bhat, G.; Lavanya, S. (Indian Journal of Fisheries, 2013)
A bloom of the dinoflagellate Noctiluca scintillans (Macartney) with a cell density of 10.5 lakh cells l-1 was observed along the Mangalore coast on 12th May 2011. The high wind velocity during the period caused further movement and dispersion of the bloom and its presence was observed 250 km away from Mangalore at Karwar by 2nd June 2011. A comparison of the nutrients in the water samples from January to May 2011 with the corresponding period during the previous year showed that the levels of silicate (26.86 Âµg-at l-1), nitrate (59.47Âµg-at l-1) and total suspended solids (61mg l-1) were highest during March 2011 in the bloom area. It was observed that the average wind velocity during January to May was 4.4 km h-1 (2010) and 8.6 km h-1 (2011) respectively. During the first week of June, a total rainfall of 206 mm was recorded. This brought down the salinity in the river as well as coastal water and the bloom completely disappeared. Significant correlation was observed between rainfall and silicate in 2010 (p